1997
DOI: 10.1093/jaoac/80.4.883
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Domestic and Imported Apples and Rice by the U.S. Food and Drug Administration Pesticide Program

Abstract: In 1993-94, the U.S. Food and Drug Administration (FDA) conducted a statistically based study of pesticide residues in domestic and imported fresh apples and processed rice. For apples, 769 domestic and 1062 imported samples were collected and analyzed; 85% of the domestic and 86% of the imported samples had detectable residues. Benomyl, a widely used fungicide, was found with greatest frequency in domestic apples, while diphenylamine was found most often in imported apples. One domestic and 4 imported samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Helicopter technique (single application) has the benefit of treating large areas with greater efficiency in a shorter time at relatively low cost. Many methods were published in the literature for the determination of residues of endosulfan and its metabolites in fruits and vegetables, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] meat, 23 dairy and milk pro-ducts, [24][25][26][27] soil, 28,29 water [30][31][32][33][34] and plant and animal tissue. [35][36][37][38][39][40] The environmental fate and behaviour of the compound has been extensively studied.…”
Section: Introduction Endosulfanmentioning
confidence: 99%
“…Helicopter technique (single application) has the benefit of treating large areas with greater efficiency in a shorter time at relatively low cost. Many methods were published in the literature for the determination of residues of endosulfan and its metabolites in fruits and vegetables, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] meat, 23 dairy and milk pro-ducts, [24][25][26][27] soil, 28,29 water [30][31][32][33][34] and plant and animal tissue. [35][36][37][38][39][40] The environmental fate and behaviour of the compound has been extensively studied.…”
Section: Introduction Endosulfanmentioning
confidence: 99%
“…Azinphos-methyl (AM) is a common insecticide used for pest control. Residues of this pesticide have been found in apples, tomatoes, oranges, and even water (Neidert and Saschenbrecker, 1996;Herna ´ndez et al, 1996;Roy et al, 1997). Their analysis is generally performed by liquid-solid extraction followed by gas chromatographic techniques, either using nitrogen phosphorus or mass spectrometric detection.…”
Section: Introductionmentioning
confidence: 99%
“…26 A study of pesticide residue in domestic processed rice was conducted by the U.S. Food and Drug Administration (FDA) in 1993−1994 and showed that levels of most pesticide residues found in processed rice were generally well below U.S. standards, and few violative residues (1.3%) were found. 27 Second, our subjects were considerably younger than those in other studies. Young children eat more fresh produce and drink more water, milk, or fruit juice than do school-age children or adolescents in proportion to body weight.…”
Section: ■ Discussionmentioning
confidence: 75%